USE OF INTERACTIVE METHODS IN WORKING WITH STUDENTS WITH LOW MASTERY IN PRIMARY GRADES - Khojamova Gulsevar (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In this article, in addition to the study of advanced foreign experiences in order to improve the quality and efficiency of education implemented in the innovative development of our country, the introduction of international standard requirements and the determination of the talent of primary school students, in the lesson International assessment of issues related to the organization of work with students who do not master and cannot master, develop programs for individual engagement with students with a loose mastery level and apply it to the field of education I tried to approach from the point of view of systems and their implementation in our country. In the article, educational technologies that serve to increase the activity of low-achieving students in the process of primary education, to create an opportunity for them to catch up with their peers, to form and develop knowledge, skills, skills and competencies in students practical application experiences are presented in an integral connection with the international PIRLS evaluation system.